Regioselective one-pot synthesis of 3-fluoro-imidazo[1,2-a]pyridines from styrene - Said, Madhukar S.; Mishra, Ankita; Pandole, Satish; Nayak, Rashmi A.; Kumar, Pradeep; Gajbhiye, Jayant M. (Asian Journal of Organic Chemistry, 2019)
A one-pot synthesis of C-3 fluorinated imidazopyridines (F-IMPY) is reported under the additive-free conditions from commercially available styrene and 1-fluoropyridinium tetrafluoroborate as a fluorine source. The substrate styrene undergoes keto-bromination/condensation/fluorination transformation in three sequential steps to furnish F-IMPY. This one-pot synthesis method exhibits broad substrate scope and good functional group tolerance with a good yield (up to 82%).
Keywords: fluorination; imidazopyridines (F-IMPY); One-pot synthesis

Retraction: organocatalytic stereoselective synthesis of passifloricin A (Retraction of Vol 10, Pg 1820, 2012) - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2019)